Un/natural death and extinction. Issue 4 (5th December 2018) - Largen, Kristin Johnston
Abstract: This article examines the question of death in the larger context of extinction, more specifically in the context of the sixth extinction, the human‐caused mass die‐off of species we are currently experiencing.  The point is made that while both death and extinction are a natural part of evolutionary life on earth, there are critical aspects of both that are distinctly "unnatural"—even sinful, and should be combatted and resisted.